Functional inks and printing of two-dimensional materials. (18th April 2018) - Hu, Guohua; Kang, Joohoon; Ng, Leonard W. T.; Zhu, Xiaoxi; Howe, Richard C. T.; Jones, Christopher G.; Hersam, Mark C.; Hasan, Tawfique
Abstract : Functional printing of graphene and related two-dimensional materials provides an ideal platform for next generation disruptive technologies and applications. Abstract : Graphene and related two-dimensional materials provide an ideal platform for next generation disruptive technologies and applications. Exploiting these solution-processed two-dimensional materials in printing can accelerate this development by allowing additive patterning on both rigid and conformable substrates for flexible device design and large-scale, high-speed, cost-effective manufacturing. In this review, we summarise the current progress on ink formulation of two-dimensional materials and the printable applications enabled by them. We also present our perspectives on their research and technological future prospects.